Whole‐lake experiments reveal the fate of terrestrial particulate organic carbon in benthic food webs of shallow lakes. Issue 6 (1st June 2014) - Scharnweber, K.; Syväranta, J.; Hilt, S.; Brauns, M.; Vanni, M. J.; Brothers, S.; Köhler, J.; Knežević-Jarić, J.; Mehner, T.
Abstract : Lake ecosystems are strongly linked to their terrestrial surroundings by material and energy fluxes across ecosystem boundaries. However, the contribution of terrestrial particulate organic carbon (tPOC) from annual leaf fall to lake food webs has not yet been adequately traced and quantified. In this study, we conducted whole‐lake experiments to trace artificially added tPOC through the food webs of two shallow lakes of similar eutrophic status, but featuring alternative stable regimes (macrophyte rich vs. phytoplankton dominated). Lakes were divided with a curtain, and maize ( Zea mays ) leaves were added, as an isotopically distinct tPOC source, into one half of each lake. To estimate the balance between autochthonous carbon fixation and allochthonous carbon input, primary production and tPOC and tDOC (terrestrial dissolved organic carbon) influx were calculated for the treatment sides. We measured the stable isotope ratios of carbon (δ 13 C) of about 800 samples from all trophic consumer levels and compared them between lake sides, lakes, and three seasons. Leaf litter bag experiments showed that added maize leaves were processed at rates similar to those observed for leaves from shoreline plants, supporting the suitability of maize leaves as a tracer. The lake‐wide carbon influx estimates confirmed that autochthonous carbon fixation by primary production was the dominant carbon source for consumers in the lakes. Nevertheless, carbon isotope values of benthic macroinvertebrates were significantly higher with maize additions compared to the reference side of each lake. Carbon isotope values of omnivorous and piscivorous fish were significantly affected by maize additions only in the macrophyte‐dominated lake and δ 13 C of zooplankton and planktivorous fish remained unaffected in both lakes. In summary, our results experimentally demonstrate that tPOC in form of autumnal litterfall is rapidly processed during the subsequent months in the food web of shallow lakes and is channeled to secondary and tertiary consumers predominantly via the benthic pathways. A more intense processing of tPOC seems to be connected to a higher structural complexity in littoral zones, and hence may differ between shallow lakes of alternative stable states.